Plasma membrane H+-ATPase Pma1 regulates growth and virulence in Penicillium digitatum from citrus fruits involving iron homeostasis - Xinyue Lin; Huilin Kang; Shuzhen Yang; Gang Fan; Litao Peng; Hanyu Mu; Yanli Wang (Food Microbiology, 2026)

Mechanisms ofra Tetmethylpyrazine in spinal cord injury: a narrative review - Yu Jiang; Gang Liu; Huizhong Bai; Jiashu Yue; Bowen Deng; Feng Gao; Jinyu Li; Xiaohong Mu (Molecular Biology Reports, 2026)

The multicopper ferroxidase Pdfet3 is essential for reductive iron assimilation, redox homeostasis, and virulence in Penicillium digitatum - Xinyue Lin; Shuzhen Yang; Hanyu Mu; Gang Fan; Litao Peng; Yanli Wang (Physiological and Molecular Plant Pathology, 2026)

Multi-response calibration and validation of a DEM for wet Mactra veneriformis–mudflat sediment mixtures during mechanised harvesting - Hangqi Li; Gang Mu; Bin Xu; Guangcong Chen; Guochen Zhang; Xiuchen Li (Biosystems Engineering, 2026)

Enhancing composite emulsion stability through electrostatic modulation of polysaccharides-whey protein isolate interactions for probiotic encapsulation - Wei-Gang Xin; Yu-Hang Jiang; Yu-Han Dong; Yu-Hang Hou; Mu-Ying Du; Amel Ahmed Ibrahim; Zsolt Zalán; Hua-Yi Suo (Food Chemistry, 2026)

Enhanced biomethane production associated with olivine-stimulated CO2 reduction in petroleum reservoir production water - Muhammad Javed; Muhammad Irfan; Le-Gang Chen; Bo Fang; Bo-Wen Wang; Ghulam Dastgir; Muhammad Kashif Javed; Lei Zhou; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

Land-use change dominates amphibian biodiversity loss, with antagonistic interactions with climate change in the karst region of Guizhou, China - Jing Liu; Shize Li; Gang Wei; Tuo Shen; Lang Mu; Haijun Su (Journal of Environmental Management, 2026)

TME-activated MXene nanoheterojunctions engineer cancer cells through phototherapy and metabolic interference for enhanced cuproptosis and immunotherapy - Hui Li; Jie Geng; Min Mu; Susu Xiao; Chenqian Feng; Lihua Zhou; Yuanxiang Wang; Wei Yu; Rangrang Fan; Bo Han; Gang Guo (Chemical Engineering Journal, 2026)

Genome-wide investigation of methyl-CpG-binding domain genes in Brassica napus L. and functional characterization of BnaC09.MBD7 and BnaA10.MBD7 in modulating osmotic stress tolerance - Ling Jiang; Gang Lin; Mufei Shi; Jingying Wu; Lixuan Sun; Xiumei Xu; Zhihua Zhang; Shiyao Wen; Meifeng Chen; Xiewang Gao; Mu Xiao (Physiology and Molecular Biology of Plants, 2026)

Engineering-designed NIR-II carbon dots: for liver and gallbladder diagnosis and treatment - Huixian Mao; Qianwen Mu; Zhixiang Lu; Gang Liu (Science Bulletin, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A simplified empirical ocean current profile model for offshore engineering from wind–wave inputs using Buckingham Π and depth-recursive reconstruction - Yun-Mu Jiang; Gang Li; Ding-Hao Yu; Zhi-Qian Dong (Ocean Engineering, 2026)

Alterations in the ecological amplitude of summer-dormant submerged macrophyte serve as sensitive indicators for the ecological risk of PFAS in water - Zhenhan Li; Hongwei Yu; Diga Gang; Quanlin Lu; He Ji; Jichun Mu; Xiaoyan Zheng; Jing Qi; Chengzhi Hu; Jiuhui Qu (Journal of Hazardous Materials, 2026)

Hybrid energy system based on co-firing municipal sludge coupled with power generation: energy balance, carbon emissions, and thermo-economic analysis - Zhaolei Meng; Zongguo Wen; Xin Meng; Fan Fei; Yanfei Mu; Gang Li; Tao Zhou; Quanjie Li; Yiqun Meng (Journal of Cleaner Production, 2026)

Synergistic cross-linked network and electron-rich 0D/1D heterostructure enable high-performance PEO-based lithium metal batteries - Tengxiao Mu; Chen Wen; Yongsheng Yao; Min Li; Gang Wang; Liwen Yang; Zengsheng Ma; Guobao Xu (Chemical Engineering Journal, 2026)

Treatment of shale gas fracturing flowback fluid using a novel multistage flocculation reactor: Energy-matching mechanism and field validation - Xing Liang; Can Cui; Lulu Xu; Yumin Mu; Gang Jin; Chang Liu; Liang Li; Haijun Zhang; Xiaobing Li (Process Safety and Environmental Protection, 2026)

Valorization of steelmaking dust into an Fe-C persulfate catalyst for eco-efficient PAHs degradation in soil - Yumin Mu; Chang Liu; Gang Jin; Congcong Li; Tongtong Xia; Xing Liang; Xiaobing Li (Process Safety and Environmental Protection, 2026)

Bioconversion of CO2 to methane energy by Methanococcus maripaludis in newly-designed bioreactor system: Kinetic characteristics, parameter optimization and grid-quality production - Lei Zhou; Jie Gao; Le-Gang Chen; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

Optimized Design and Experimental Evaluation of a Vibratory Screening Unit for Mactra veneriformis Harvesting on Intertidal Mudflats Based on the Discrete Element Method - Bin Xu; Shuyuan Liang; Yuzhong Lou; Jixuan Zhao; Hangqi Li; Yizhi Chang; Hao Wu; Guangcong Chen; Gang Mu (Fishes, 2025)
To enhance shell–mud separation and overall harvesting efficiency for Mactra veneriformis under intertidal mudflat conditions, a vibratory harvesting device driven by a crank–rocker mechanism that produces approximately rectilinear simple-harmonic motion was developed. Dynamic analysis of clam motion on the screen deck identified vibration amplitude, vibration frequency, excitation direction angle, and screen deck inclination angle as key determinants of screening performance. Single-factor tests, a Plackett–Burman design, a steepest-ascent experiment, and response surface methodology (RSM) optimization were conducted. Their influences on forward travel speed ranked as follows: screen deck inclination angle > excitation direction angle > vibration amplitude > vibration frequency. The optimized settings were vibration amplitude of 8.5 mm, excitation direction angle of 45°, screen deck inclination angle of 11°, and vibration frequency of 10 Hz. Intertidal mudflat trials yielded a harvesting efficiency of 342 kg/h and a clam breakage rate of 4.6%, meeting the design targets. After harvesting, the shear strength of the mudflat decreased, with disturbance mainly confined to the surface layer, thereby meeting the low-disturbance requirement and enabling ecologically friendly harvesting. These results provide a basis for the design and optimization of M. veneriformis harvesting machinery.

Delayed algal blooms to runoff surges in low-runoff estuaries: hydrodynamic and nutrient driving mechanisms and early warning strategies - Linlin Wang; Zuoyi Chen; Gang Wang; Yike He; Lin Mu; Xianzhong Mao; Hongsheng Bi; Jiabo Zhang (Journal of Hydrology, 2025)

Cross-scale mechanisms of surfactant-enhanced phenanthrene desorption from mineral-water interfaces: Integrating molecular dynamics and experimental insights - Tongtong Xia; Yumin Mu; Congcong Li; Gang Jin; Chang Liu; Xing Liang; Xiaobing Li (Chemical Engineering Journal, 2025)

Design and testing of the clam vibration harvester's V-shaped double-spiral harvesting roller brush based on DEM-MBD - Li Hangqi; Mu Gang; Li Xiuchen; Wu Hao; Xu Bin; Liu Fawei; Sun Zhenyin; Zhang Qian; Zhang Hanbing; Xin Mingjin; Zhang Guochen (Aquacultural Engineering, 2025)

Mechanical Characterization and Dual-Layer Discrete Element Modeling of Mactra veneriformis - Bin Xu; Yazhou Yang; Hangqi Li; Guangcong Chen; Yizhi Chang; Feihong Guo; Hao Wu; Jixuan Zhao; Zijing Liu; Guochen Zhang; Xiuchen Li; Hanbing Zhang; et al. (Fishes, 2025)
The discrete element model of Mactra veneriformis currently employs an oversimplified multi-sphere approach using EDEM’s Hertz–Mindlin model, assuming uniform shell–flesh mechanical properties. This study developed an advanced dual-layer flexible bonding model through comprehensive biomechanical testing. Mechanical properties and shell morphology were experimentally characterized to inform model development. Parameter optimization combined free-fall experiments with Plackett–Burman screening, steepest ascent method, and Box–Behnken RSM, yielding optimal contact parameters: flesh–flesh stiffness (X1) = 3.64 × 1011 N/m3, shell–flesh interface (X3) = 1.48×1013 N/m3, shell–shell tangential stiffness (X6) = 3.23 × 1012 N/m3, and normal strength (X7) = 8.35 × 106 Pa. Validation showed only 4.89% deviation between simulated and actual drop tests, with hydraulic impact tests confirming excellent model accuracy. The developed model accurately predicts mechanical behavior and shell fracture patterns during harvesting operations. This research provides a validated numerical tool for optimizing clam cultivation and harvesting equipment design, offering significant potential to reduce shell damage while improving harvesting efficiency in bivalve aquaculture systems.

Exploring Morphological Indicators for Ramet Age Discrimination of Fargesia nitida Based on Growth Patterns - Xiu-xin Mu; Kai-ming Lei; Hong-ou Sun; Pei-gang Kuang; Yue Zhang; Guo-lan Wang; Tao Zeng (Journal of Plant Growth Regulation, 2025)

Biogeography and Niche Evolution of Odorrana schmackeri Complex in Southern China - Shize Li; Bin Wang; Jing Liu; Haijun Su; Gang Wei; Lang Mu; Tuo Shen; Zhitong Lyu; Yingyong Wang; Houqiang Xu (Journal of Biogeography, 2025)
Aim The Odorrana schmackeri complex (OSC), widely distributed across southern China, presents intriguing mysteries regarding its diversification dynamics. Resolving these evolutionary enigmas would establish a crucial foundation for understanding biogeographic evolution in this topographically complex region. Therefore, we integrated phylogenetic, demographic, and ecological niche analyses to elucidate the roles of ancient tectonism, Quaternary climatic fluctuations, and niche evolution in shaping its diversification and distribution. Location Southern China. Methods Using two mitochondrial and eight nuclear genes, we reconstructed phylogenetic relationships, estimated divergence times and assessed population dynamics. Ecological niche models (ENMs) were optimised via the ‘Kuenm’ package, and niche overlap, equivalency, and similarity were quantified using the ‘ecospat’ R package. Acestral niche and climatic tolerances reconstruction were used in the ‘phyloclim’ package. Results The OSC comprises nine species and originated from a mid‐Miocene ancestor (~12.55 Ma). Mitochondrial phylogeny resolved four deeply divergent clades, while nuclear gene phylogeny revealed incomplete lineage sorting (ILS) and historical gene flow (STRUCTURE, K = 7; JML, p > 0.05). Post‐last glacial maximum (LGM) expansions (~0.02 Ma) facilitated secondary contact in sympatric zones, where niche conservatism dominated between sister species. Ancestral niche reconstruction identified precipitation variables as key drivers of early divergence, while thermal tolerances evolved conservatively. The results indicated that Miocene uplift of the Qinghai‐Tibet Plateau (~12.55–8.70 Ma) promoted southward expansion, while Pliocene‐Pleistocene (~5.58–2.40 Ma) river reorganisations fragmented and later connected populations. Main Conclusions The OSC's diversification reflects the interplay between Miocene–Pliocene tectonism and Quaternary climatic cycles. While ancestral niche divergence along precipitation gradients initiated speciation, post‐LGM sympatry favoured conservatism in thermal microhabitats. Combining multilocus phylogenetics, demographic inference, and niche modelling resolves the rapid‐radiating models in the frog complex and highlights the dynamic roles of landscape features in shaping biogeographic patterns of them.

A robust CMCNa-PAM salt-inhibiting double-network hydrogel for efficient solar interfacial evaporation - Junzhe Huang; Jianhua Zhou; Yang Long; Xiaojiang Mu; Zhixiang Zhang; Yanqing Zhu; Gang Xu; Jing Liu; Jun-Liang Chen; Lei Miao (Journal of Environmental Chemical Engineering, 2025)

Recommendations on benchmarks for the DeNitrification–DeComposition model application in China: Insights from literature analysis - Nanchi Shen; Jiani Tan; Qing Mu; Ling Huang; Wenbo Xue; Yangjun Wang; Maggie Chel Gee Ooi; Mohd Talib Latif; Gang Yan; Lam Yun Fat Nicky; Li Li (Environmental Modelling & Software, 2025)

Heat Deficit for Vegetation Leaf Senescence and Its Key Accumulation Process and Determinants at Northern Middle and High Latitudes During 2001–2022 - Zhihui Yuan; Gang Bao; Fei Li; Jiquan Chen; Jingfeng Xiao; Qier Mu; Enliang Guo; Siqin Tong; Sainbuyan Bayarsaikhan (Global Ecology and Biogeography, 2025)
Aim Cold degree days (CDD) represent the heat deficit for vegetation leaf senescence in autumn and serve as a critical parameter in modelling leaf senescence. This study aimed to quantify the spatiotemporal patterns of CDD and its key accumulation processes and determinants. Location At northern middle and high latitudes (> 30° N). Period 2001–2022. Major Taxa Studied Vegetation. Methods We estimate CDD as the cumulative sum of the difference between the daily mean temperature and a threshold temperature (12.75°C) during the period from midsummer to the end of the growing season. To identify its crucial metric, we employ a combination of grey relational analysis, random forest model and partial correlation analysis. Results The average CDD increases linearly with latitude at a rate of 5.9°C‐days per degree. Higher latitudes exhibit larger CDD (> 300.0°C‐days), longer accumulation periods (> 70 days) and faster accumulation rates (> 6.0°C/day), whereas lower latitudes show smaller CDD ( 46% of the study area, especially at high latitudes and on the Tibetan Plateau. While climate warming generally reduces CDD, an increase in precipitation frequency can counteract this trend and shape the relationship between precipitation amount and CDD. The effects of radiation and wind speed on CDD were less pronounced than those of precipitation frequency, with wind exerting a positive (cooling) effect that increases CDD accumulation and radiation producing a negative (heating) effect that decreases CDD accumulation. Main Conclusions This study highlights the critical aspects of the CDD accumulation process and emphasises the importance of incorporating precipitation frequency into CDD‐based autumn phenology models across northern latitudes.

Photo-stimulating dual-network microminiature hydrogels reinforced with silver sulfide nanoparticles for regulated cancer photothermal therapy - Rongqiu Mu; Guanghui Gu; Youyin Xu; Yongming Xi; Gang Wei (Chemical Engineering Journal, 2025)

Crystal adjustment-based neutral-tinted nickel-tungsten-oxygen for electrochromic energy-efficient windows with wide spectral regulation - Aiyan Shi; Guojian Yang; Awais Ghani; Qinye Lu; Wenxin Ye; Chenjie Mu; Tengyao Jiang; Zhenqian Pang; Yanghua Lu; Gang Tan (Chemical Engineering Journal, 2025)

A fusion of oncolytic viruses and bispecific T-cell engagers for triple negative breast cancer immunotherapy - Min Mu; Hui Li; Guoqing Wang; Bo Chen; Rangrang Fan; Nianyong Chen; Bingwen Zou; Aiping Tong; Gang Guo (Chemical Engineering Journal, 2025)

Structure-selectivity relationship of anion exchange resins with different quaternary amine functional groups for highly selective removal of PFAS from chromium-plating wastewater - Xiangzhe Jiang; Yihua Luo; Shuang Mu; Bojiang Meng; Wei Wang; Gang Yu; Shubo Deng (Water Research, 2025)

Phase-separated anisotropic PVA hydrogel loaded with tetramethylpyrazine for spinal cord injury repair - Gang Liu; Shenglin Li; Bowen Deng; Luyao Huo; Huizhong Bai; Shengyuan Jiang; Yimin Zhou; Zhenzhen Pei; Ceren Kimna; Yi Zhao; Lin Xu; Jinyu Li; et al. (Chemical Engineering Journal, 2025)

Comparative life cycle assessment of various hydrogen supply methods from Australia to the Republic of Korea in environmental and economic aspects - Gang Nam Lee; Jong Mu Kim; Kwang Hyo Jung; Hyun Park (Science of The Total Environment, 2024)

Nutrient requirements determined by grain yield and protein content to optimize N, P, and K fertilizer management in China - Xuemei Zhang; Zikang Guo; Junfeng Xu; Cui Huang; Haiyan Dang; Wenyan Mu; Lulu Zhang; Saibin Hou; Ning Huang; Chao Li; Yulan Ding; Ruiqing Sun; et al. (Science of The Total Environment, 2024)

Toward a Learnable Climate Model in the Artificial Intelligence Era - Gang Huang; Ya Wang; Yoo-Geun Ham; Bin Mu; Weichen Tao; Chaoyang Xie (Advances in Atmospheric Sciences, 2024)

Experimental study on flow kinematics and pressure characteristics of dam break flow - Hyung Joon Kim; Jong Mu Kim; Jae Hong Kim; Kwang Hyo Jung; Gang Nam Lee (Ocean Engineering, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

Enhanced carbon dioxide sequestration and Cr detoxification: Direct carbonation of AOD slag with additives under ambient conditions - Haolei Wang; Gang Zhou; Yuanqiong Mu; Mei Zhang; Min Guo (Journal of Cleaner Production, 2024)

Dynamic responses of multi-story structural systems with separated gravity and lateral resisting systems under seismic action considering connection semi-rigidity effects - He Zhao; Xin-Yu Qian; Xiao-Gang Liu; Hong-Bing Chen; Mu-Xuan Tao (Engineering Structures, 2024)

Pilot-scale removal of PFAS from chromium-plating wastewater by anion exchange resin and activated carbon: Adsorption difference between PFOS and 6:2 fluorotelomer sulfonate - Xiangzhe Jiang; Ziming Zhou; Dongsheng Wang; Guocheng Liu; Wei Wang; Shuang Mu; Gang Yu; Shubo Deng (Chemical Engineering Journal, 2024)

Assessment of annual variability in the population status and reproductive cycle of purple sea urchins (Heliocidaris crassispina, Agassiz, 1864) in Daya Bay, China - Xinye Zhao; Xiaohui Mu; Yu Guo; Jiayang Li; Zhenhua Ma; Gang Yu; Chuanxin Qin (Frontiers in Marine Science, 2024)
The purple sea urchin ( Heliocidaris crassispina ) is one of the main drivers of ecosystem dynamics, and its reproductive cycle plays an important role in population structure and size variability. In this study, we analyzed the population structure, gonadal developmental characteristics, reproductive cycle and other factors influencing wild purple sea urchins from December 2021 to November 2022 in Daya Bay, Guangdong, China. The results showed that purple sea urchins showed an allometric growth pattern, there were obvious seasonal variations in the population size, and fishing pressure reduced the sea urchin populations; two-factor analysis of variance (ANOVA) and correlation analyses showed negative correlations between month (M), test diameter (TD), weight (W) and gonadal index (GI) ( P > 0.01), and a positive correlation between TD, weight (W), and GI ( P <0.01); the gonadal development process can be divided into recovery, growth, prematuration, maturation, and late discharge, with almost synchronous development of male and female gametes; the spawning period is from April to November, which is longer than in the temperate zones, showing two spawning peaks in April and August. The time of spawning is influenced by temperature and food. Data on the breeding cycle of sea urchins in Daya Bay were obtained in this study. This information can offer theoretical assistance in the preservation and management of both artificial nurseries and wild resources.

Metabolic degradation of polysaccharides from Lentinus edodes by Kupffer cells via the Dectin-1/Syk signaling pathway - Yu Zhang; Wenqi Tang; Ziming Zheng; Gang Nie; Yuxue Zhan; Xu Mu; Yuxuan Liu; Kaiping Wang (Carbohydrate Polymers, 2023)

Numerical study of the unsteady crosswind response of high-speed train under local structure-induced unsteady winds by MBS - Dongqin Zhang; Mu Zhong; Gang Hu; Yiqing Xiao (Engineering Structures, 2023)

Applicability analysis of thermosyphon for thermally stabilizing pipeline foundation permafrost and its layout optimization - Fei Wang; Guoyu Li; Fedorov Alexander; Wei Ma; Dun Chen; Gang Wu; Yanhu Mu; Xinbin Wang; Hongyuan Jing; Zhenrong Zhang (Cold Regions Science and Technology, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Design and testing of a mechanized brush-screen cooperative vibration harvester for mudflat-buried shellfish based on the discrete element method - Hangqi Li; Gang Mu; Hanbing Zhang; Hao Wu; Fawei Liu; Zhenyin Sun; Qian Zhang; Yizhou Wang; Yurui Wang; Xiuchen Li; Guochen Zhang (Frontiers in Marine Science, 2023)
Introduction To enhance the application of mechanized harvesting and supplement research on harvesting theory in mudflat-buried shellfish harvesting in China, a brush-screen cooperative mudflat-buried shellfish vibration harvester was designed. Methods The harvester is primarily composed of a crank rocker double-layer vibrating screen, two stage rolling brush, and a conveyor chain. White clams ( Mactra veneriformis ) cultured in mudflats were used as the research objects in this paper, and the mechanics and motion states of the shellfish on the vibrating screen were analyzed. The shellfish harvesting simulation response surface experiments based on the discrete element method (DEM) were conducted to analyze the influence of the main operating parameters on the quantity of shellfish harvested. Results The results revealed that the number of shellfish harvested was significantly influenced ( p < 0.01) by vibrating screen amplitude, first-stage spiral rolling stainless steel brush rotation rate, and harvester travel speed. The optimal combination of key parameters was 1.4 mm, 40 rpm, and 10 m/min, respectively. With these values, the projected shellfish crushing rate was 2.82% and the shellfish harvesting efficiency was 125 pieces/m 2 . The equipment was then manufactured and the shellfish harvesting verification test was performed under the same operating parameters as the simulation. Test results indicated that the harvesting efficiency of the equipment was 114 pieces/m 2 and the shellfish crushing rate was 6.97%. Discussion The shellfish harvesting work could be completed by the equipment effectively and with low loss. The results of this study provide a theoretical reference for a novel mechanized method of harvesting mudflat-buried shellfish.

Design and experiment of cone disk centrifugal shellfish seeding device - Hanbing Zhang; Pengpeng Li; Haonan Zhang; Wei Huang; Guochen Zhang; Gang Mu; Xiuchen Li (Frontiers in Marine Science, 2023)
This paper designed a centrifugal shellfish seeding device with a conical disc structure to improve the seeding efficiency and uniformity of the centrifugal shellfish seeding device. The dynamic model of the shellfish seedling moving on the conical disk is established, and the main parameters affecting the shellfish seedling’s movement characteristics are determined as the cone angle of the impeller, the speed of the impeller, and the offset angle of the blade. Using the EDEM software and the shellfish seedlings blanking rate as the influencing factors, a single factor simulation test was performed. The research found that the variation trend of shellfish seedlings distribution in a single statistical area gradually decreased along the horizontal direction of both sides, with the origin being the center of the seedling sowing device. Test orthogonal rotation simulations using the variation coefficient of seedlings distribution uniformity and the effective job width as evaluation indicators. Use Design Expert software to optimize the structure of the seedling sowing device based on the test results, and determine the optimal structure with the maximum width and the minimum variation coefficient as constraints: the impeller cone angle is 7.72°, and the blade offset angle is -0.9°. Use the above-mentioned seeding device for simulation and actual seeding testing. The simulation results show that when the impeller speed is 750r/min and the blanking rate is 0.65kg/s, the variation coefficient of seedlings distribution uniformity and the effective job width are 12.84% and 24.98m, respectively, while the actual test results are 13.77% and 23.25m, respectively. The object of the seeding performance test was commonly used size shellfish seedlings of the Philippines clam. The results showed that the impeller speed, blanking rate, quadratic term of shellfish seedling size, quadratic term of blanking rate, and interactive term of impeller speed and blanking rate had significant effects on the variation coefficient of the distribution uniformity of shellfish seedlings ( P <0.01). Shellfish seedling size, impeller speed, and interactive term of impeller speed and blanking rate all had a significant impact on job width ( P <0.01). The results of this study provide a reference for the mechanized design of shellfish seeding.

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

High-efficient and recoverable Mo72V30@Fe3O4/C catalyst for oxidation of hydroxyfurfural - Mengdi Gong; Xin-Yu Wang; Mu-Qin Li; Wen-Xia Mu; Yun-Dong Cao; Hong Liu; Yu-Guang Lv; Xin-Hua Qi; Guang-Gang Gao (Fuel, 2023)

Graphene induced structure and doping level tuning of evaporated CsPbBr3 on different substrates - Zhaorui Wen; Yunlei Zhong; Bingchen He; Gang Wang; Shengwen Li; Zhen Mu; Jielei Li; Junpeng Xie; Yi Zheng; Guichuan Xing; Guo Hong; Shi Chen (Chemical Engineering Journal, 2023)

Sensor Partitioning Placements via Random Walk and Water Quality and Leakage Detection Models within Water Distribution Systems - Tianwei Mu; Manhong Huang; Shi Tang; Rui Zhang; Gang Chen; Baiyi Jiang (Water Resources Management, 2022)

Environmental Life-Cycle Assessment of Eco-Friendly Alternative Ship Fuels (MGO, LNG, and Hydrogen) for 170 GT Nearshore Ferry - Gang Nam Lee; Jong Mu Kim; Kwang Hyo Jung; Hyun Park; Hag Soo Jang; Chung Seong Lee; Ji Won Lee (Journal of Marine Science and Engineering, 2022)
With increasing concerns about environmental pollution, the shipping industry has been considering various fuels as alternative power sources. This paper presents a study of the holistic environmental impacts of eco-friendly alternative ship fuels of marine gas oil (MGO), liquefied natural gas (LNG), and hydrogen across each of their life cycles, from their production to the operation of the ship. The environmental impacts of the fuels were estimated by life-cycle assessment (LCA) analysis in the categories of well-to-tank, tank-to-wake, and well-to-wake phases. The LCA analysis was targeted for a 170 gross tonnage (GT) nearshore ferry operating in the ROK, which was conceptually designed in the study to be equipped with the hydrogen fuel cell propulsion system. The environmental impact performance was presented with comparisons for the terms of global warming potential (GWP), acidification potential (AP), photochemical ozone creation potential (POCP), eutrophication potential (EP), and particulate matter (PM). The results showed that the hydrogen showed the highest GWP level during its life cycle due to the large amount of emissions in the hydrogen generation process through the steam methane reforming (SMR) method. The paper concludes with suggestions of an alternative fuel for the nearshore ferry and its production method based on the results of the study.

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

The regulation of the small-conductance calcium-activated potassium current and the mechanisms of sex dimorphism in J wave syndrome - Mu Chen; Yudong Fei; Tai-Zhong Chen; Yi-Gang Li; Peng-Sheng Chen (Pflügers Archiv - European Journal of Physiology, 2021)

Quantitative Determination of Trace Lipopeptide Using HPLC through Double Carboxyls Labelling - Shi-Zhong Yang; Hong-Zhi Quan; Jin-Feng Liu; Hong-Ze Gang; Bo-Zhong Mu (International Journal of Peptide Research and Therapeutics, 2020)

Anti-breast cancer triterpenoid saponins from the thorns of Gleditsia sinensis - Jinqian Yu; Gang Li; Yan Mu; Honglei Zhou; Xiao Wang; Peng Yang (Natural Product Research, 2019)

Foliar nutrient resorption responses of three life-form plants to water and nitrogen additions in a temperate desert - Gang Huang; Yan-gui Su; Xiao-han Mu; Yan Li (Plant and Soil, 2018)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Characterization of the prokaryotic diversity through a stratigraphic permafrost core profile from the Qinghai-Tibet Plateau - Weigang Hu; Qi Zhang; Tian Tian; Dingyao Li; Gang Cheng; Jing Mu; Qingbai Wu; Fujun Niu; Lizhe An; Huyuan Feng (Extremophiles, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Ectopic WWOX Expression Inhibits Growth of 5637 Bladder Cancer Cell In Vitro and In Vivo - Gang Li; Longfeng Sun; Zhongyi Mu; Yan Huang; Cheng Fu; Bin Hu (Cell Biochemistry and Biophysics, 2015)

Characterization of the Aggregation-Induced Enhanced Emission of N,N′-bis(4-methoxysalicylide)benzene-1,4-diamine - Fuyong Wu; Guangjun Xu; Xi Zeng; Lan Mu; Carl Redshaw; Gang Wei (Journal of Fluorescence, 2015)

Introducing a salt bridge into the lipase of Stenotrophomonas maltophilia results in a very large increase in thermal stability - Jian-Ping Wu; Mu Li; Yong Zhou; Li-Rong Yang; Gang Xu (Biotechnology Letters, 2015)

The Protective Effect of a Metallic Selenopeptide with Superoxide Dismutase and Glutathione Peroxidase Activities Against Alcohol Induced Injury in Hepatic L02 Cells - Wang Cheng; Shen Na; Yan Gang-lin; Sui Chun-hong; Zhuang Jian-jian; Lü Shao-wu; Luo Gui-min; Mu Ying (International Journal of Peptide Research and Therapeutics, 2014)

Grassland coverage inter-annual variation and its coupling relation with hydrothermal factors in China during 1982–2010 - Wei Zhou; Chengcheng Gang; Yizhao Chen; Shaojie Mu; Zhengguo Sun; Jianlong Li (Journal of Geographical Sciences, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Structural characterization of rhamnolipid produced by Pseudonomas aeruginosa strain FIN2 isolated from oil reservoir water - Jin-Feng Liu; Gang Wu; Shi-Zhong Yang; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2014)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Spatio-temporal dynamics of vegetation coverage and its relationship with climate factors in Inner Mongolia, China - Shaojie Mu; Hongfei Yang; Jianlong Li; Yizhao Chen; Chengcheng Gang; Wei Zhou; Weimin Ju (Journal of Geographical Sciences, 2013)

HBV infection increases the risk of pancreatic cancer: a meta-analysis - Gang Luo; Ning-Bo Hao; Chang-Jiang Hu; Xin Yong; Mu-Han Lü; Bo-Jun Cheng; Yao Zhang; Shi-Ming Yang (Cancer Causes & Control, 2013)

Insulin-like growth factor 1 enhances the proliferation and osteogenic differentiation of human periodontal ligament stem cells via ERK and JNK MAPK pathways - Yan Yu; Jinquan Mu; Zhipeng Fan; Gang Lei; Ming Yan; Sainan Wang; Chunbo Tang; Zilu Wang; Jinhua Yu; Guangdong Zhang (Histochemistry and Cell Biology, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Molecular basis of the internalization of bovine immunodeficiency virus Tat protein - Gang Deng; Yang Su; Junjie Mu; Rina Sha; Yunqi Geng; Wentao Qiao; Qimin Chen (Virus Genes, 2008)

Mitochondrial DNA sequence polymorphisms of five ethnic populations from northern China - Qing-Peng Kong; Yong-Gang Yao; Mu Liu; Shu-Ping Shen; Cai Chen; Chun-Ling Zhu; Malliya Gounder Palanichamy; Ya-Ping Zhang (Human Genetics, 2003)